A Hybrid Mechanism for Auto Text Categorization in Web Documents - Yogi, Manas Kumar; Kalyan, Ch Manikanta; Aiswarya, Dwarampudi (Journal of Soft Computing Paradigm, 2023)
Web personalization has become such a popular paradigm nowadays, that almost all e-commerce websites are including it in their websites. The main objective of web personalization is driven by grouping similar web pages. The text categorization principle becomes a challenge when daily users visit numerous pages. This paper develops a hybrid framework which categorizes the text extracted from a web document, by applying Neighbourhood Preserving Embedding algorithm and then Particle Swarm Optimization algorithm on the extracted text groups, resulting into a group of web documents which contain similar texts. The proposed mechanism relatively has a high performance which improves with time, and as the size of web documents increase, the particle swarm algorithm also evolves in its nature.
Keywords: Embedded; particle swarm optimization; dimensionality; text categorization